Efficacy of a polyvalent injectable vaccine against Flavobacterium psychrophilum administered to rainbow trout (Oncorhynchus mykiss L.). Issue 2 (6th December 2018) - Hoare, Rowena; Jung, Sung‐Ju; Ngo, Thao P. H.; Bartie, Kerry L.; Thompson, Kim D.; Adams, Alexandra
Abstract: Flavobacterium psychrophilum is one of the most important pathogens affecting cultured rainbow trout ( Oncorhynchus mykiss ). Recent information from UK salmonid farms showed country‐wide distribution of genetically and serologically divergent clones, which has hampered the development of a vaccine for rainbow trout fry syndrome. The current study assessed the efficacy of an injectable polyvalent vaccine containing formalin‐inactivated F. psychrophilum in rainbow trout. The vaccine was formulated with an oil adjuvant (Montanide ISA 760VG) or formalin‐killed cells alone. Duplicate groups of trout (60 ± 13 g) were given phosphate‐buffered saline or vaccine formulated with Montanide by intra‐peritoneal (i.p.) injection and challenged by intra‐muscular (i.m.) injection with a homologous and a heterologous isolate of F. psychrophilum at 525 degree days post‐vaccination (dd pv). Significant protection was achieved in vaccinated fish ( p  = 0.0001, RPS 76% homologous, 88% heterologous). Efficacy of the adjuvanted vaccine was also demonstrated by heterologous challenge at 1155 dd pv resulting in 100% protection, whereas survival in the un‐adjuvanted group was not significantly different from control fish. Levels of specific antibody at 1155 dd pv, as measured by ELISA, were significantly higher in the fish vaccinated with adjuvant when compared with unvaccinated fish.